Drucke in der «Neuen Rundschau» - Walser, Robert (Robert Walser - Kritische Ausgabe sämtlicher Drucke und Manuskripte, 2019)
In this volume, Robert Walser's contributions printed in the journal "Neue Rundschau" are edited. Each of Walser's texts is accompanied by a context documentation, which gives an insight into the contents of the whole journal issue. In the editors' afterword, Walser's relations with the journal and with the publisher S. Fischer are described. A documentary appendix with letters and further material illustrates the relations between Walser and the editors.